A Durable Replacement Model for Symbolic Vs. Utilitarian Consumption: An Integrated Cultural and Socio-Economic Perspective - YOO, Shijin (Institutional Knowledge at Singapore Management University, 2006)
The accumulated knowledge on durable consumption has traditionally been premised upon identifying personal factors (e.g. demographics or psychographics) underlying the purchase decision. On a broader scope, however, consumer behavior is shaped by cultural and social factors, and our understanding would be incomplete without these considerations. To this end, this study sets out to provide an integrative framework on durable consumption. Specifically, the proposed framework explores whether cultural differences do exist in the perception of a selected durable (e.g. automobile) on the symbolic/utilitarian dimension, which in turn, may affect the length of the replacement cycle, likelihood of upgrading to a higher status model, as well as, inertia towards remaining within the same product-type in the category (e.g. sedan, SUV, minivan, pickup truck). Applying a multinomial logit model to Korean and US automobile transaction data, the finding reveal that Korean consumers tend to have shorter replacement cycles, engage in more upgrades but are less likely to change the product-type than American consumers. Considerations of cultural and socio-economic factors as key drivers of the differences in perception and behavior are put forward. Managerial implications and directions for future research are also discussed.